Caught in a crossfire: Front-end decision-making in airport expansion programmes - Pierpaolo Avanzi; Vedran Zerjav (Transportation Research Interdisciplinary Perspectives, 2020)
This paper revisits the main factors and considerations that drive the decision to invest in major capital projects in airport infrastructure, specifically airport expansion programmes.To this end, the paper explores how governments, operators and investors have navigated the project front-end considerations (strategic assessment, business justification, option decision, investment decision) in the planning of Heathrow, Schiphol and Dublin Airport expansion programmes. Through inductive research on publicly available material, professional conference reports, planning documentation and exploratory interviews with key personnel involved in the selected projects, the study compares and contrasts the three projects and contributes to the current debates on the role that governments have into fostering economic growth whilst taking into account environmental restriction and climate change. The goal of the study is to inform the upcoming restructuring and transformation of business models in air travel as a response to the Covid-19 crisis.